ANALYSIS OF DIRECT EXPENDITURE BUDGET REALIZATION REPORTS IN ORDER TO MEASURE EFFECTIVENESS AND EFFICIENCY AT BKAD MEDAN CITY - Muhammad Kahfi Hakim; Annio Indah Lestari Nasution; Nurwani Nurwani (SEAN Institute, 2023)
Public sector organizations are required to pay attention to Value for Money to carry out their activities. The desired goal means that it includes accountability regarding the application of value for money, namely economy in the procurement and allocation of resources that are efficient in the use of resources in the sense that their use is minimized and the results are maximized and effective in the sense of achieving goals and targets. This research is an observation that will occur which shows information and mentions the nature that occurs in the object under study. This study aims to determine and analyze the effectiveness and efficiency of the direct expenditure budget of the Regional Finance and Asset Agency in 2015-2021. in this study it can be seen whether the application of the expenditure budget of the Regional Finance and Asset Agency of Medan city has been effective and efficient in it. The type of research used in this research is descriptive research using a qualitative approach. Data collection techniques are carried out using interviews and documentation. The theory used to determine and analyze the effectiveness and efficiency of the implementation of the rules is the analysis and calculation of the level of effectiveness and efficiency. based on the results of this study, the level or criteria for the effectiveness of the rules at the Regional Finance and Asset Agency in 2015-2021 are shared. in practice, the 2015-2021 rules have been holistically effective and very efficient.